Tom Lake : a novel [compact disc, unabridged] - Patchett, Ann (HarperCollins Publishers, 2023)
In the spring of 2020, Lara's three daughters return to the family's orchard in Northern Michigan. While picking cherries, they beg their mother to tell them the story of Peter Duke, a famous actor with whom she shared both a stage and a romance years before at a theater company called Tom Lake. As Lara recalls the past, her daughters examine their own lives and relationship with their mother, and are forced to reconsider the world and everything they thought they knew. Tom Lake is a meditation on youthful love, married love, and the lives parents have led before their children were born. Both hopeful and elegiac, it explores what it means to be happy even when the world is falling apart.